Pogled na znanstveno raziskovalno delo Oddelka za geografijo od ustanovitve do danes - Vovk Korže, Ana (Revija za geografijo, 2013)
Fifty years of geography in Maribor is an opportunity to look at the scientific research activities since the beginning of 1962 until today. Bibliographies of geographers from Maribor include various activities, which included geography. Addition to the traditional division of geography on the physical, social, educational and regional geography, we have a growing number of active geographers in the field of environmental geography. The article presents a brief look at the activity area and changes in the orientation that are monitored especially since Slovenia joined the EU.
Keywords: Filozofska fakulteta; geografija; geography; Maribor; Oddelek za geografijo; znanstvenoraziskovalno delo